Characterization of dielectric barrier discharge jet for surface treatment / Choo Chee Yee - Choo, Chee Yee (2013)
Dielectric barrier discharge (DBD) under atmospheric pressure can be generated in a simple and economical way without complicated vacuum system and it has found many uses ranging from the industry to medicine. This work presents the characteristics of a filamentary dielectric barrier discharge jet (DBD jet) in Ar, N2 and Ar:N2 (47%:53%) mixture. The jet was designed based on DBD configuration which consisted of a hemispherical powered electrode, grounded end plate with nozzle and a glass test tube as the insulator. The discharge was ignited between the electrodes and gas flow across the discharge and through the 1.0 mm nozzle then formed the jet. This configuration resulted in constriction of the gas flow and the DBD was subjected to pressures above atmospheric pressure. The ignition of the jet was investigated for different kinds of gases. The ignition voltage for Ar was the lowest. The highest number of current filaments was obtained from Ar discharge while N2 discharge registered the least even though at higher ignition voltage. Influence of operating parameters (applied high voltage, gas flow rate, gap width) on the electrical characteristics (charge transferred, energy deposited and power dissipated between the electrodes) of the DBD jet for Ar, N2 and Ar:N2 was studied experimentally based on the Q-V Lissajous method. The measured mean power dissipated was less than 7 W for all the gases employed, yielding an efficiency <19%. The dielectric capacitance, Cd deduced from Q-V Lissajous plot decreased at higher gas flow rate for the gases employed in this study except in Ar discharge, in which Cd remained constant. The physical structure of the plasma jets was qualitatively analyzed from the digital images and correlated to the electrical characteristics of the DBD jet. Ar, N2 and Ar:N2 jets grew longer and wider with increase in gas flow rate. At the applied voltage of iv 14.2 kV and flow rate of 12.5 LPM, Ar jet length expanded up to 6.2 mm in open air whereas the width grew from 0.4 mm at 1.8 LPM to 1.4 mm at 12.5 LPM. These were the optimum conditions to obtain a ‘good’ jet (in terms of dimension and luminosity) in the present setup. The net charges transported in the plasma jets were measured by placing a copper disc to intercept the jet stream. The charges transported out of the nozzle were higher in N2 jet than Ar jet. The optical diagnostic of DBD jet had been employed by using a spectrometer where line intensities from the jet in Ar and N2 were observed and chemically active species of the jet were determined. The chemically active species (O, OH, N) transported through the jet are useful for surface treatment. Surface treatment was carried out for Ar and N2 discharges at various treatment times (15 s, 30 s, 60 s, 90 s, and 120 s). It was found that treated Mylar film by N2 and Ar plasma jets demonstrated ability to enhance surface wettability. The ageing effect on the Mylar film treated for 120 s showed that the sample did not fully recover to the untreated state even after 50 days of ageing.